Penggunaan Model Pembelajaran Inkuiri pada Materi Pertumbuhan dan Perkembangan Tumbuhan untuk Meningkatkan Keterampilan Proses Sains Peserta Didik - Hasan, Ani M (Postgraduate, University of Mataram, 2024)
The purpose of the study was to improve the science process skills of students by using an inquiry learning model on the material of growth and development in plants. This type of research uses quasi experimental in the form of Nonequivalent Control Group Design. The population in this study were all XII IPA classes. The samples were class XII IPA 1 and class XII IPA 2 with a total of 28 students. The sampling technique used in this study was Purposive Sampling. The data collection technique used is in the form of a test of students' science process skills. The results of the t test analysis research can be obtained sig value. (2-tailed) of 0.033 <0.05, then according to the basis for decision making in the independent sample t-test, it can be concluded that H0 is rejected and Ha is accepted, meaning that the application of the inquiry learning model on the material of growth and development in plants can improve the science process skills of students at SMA Negeri 1 Tapa. Suggestions from researchers require further research on the application of inquiry learning models on other subjects, so that it can be seen the consistency of the effect of applying these learning models on improving science process skills.